Palm oil industry: certification development - Sean Andrew Labansing; Yeo Soon Jian; Tang Chung Siong; Tracy Joann Stanlee (Penerbit UMS, 2020)
The agricultural industry has been the backbone of Sabah's economy for decades. The industry has eradicated poverty and supported connectivity between the rural with the urban area. At the same time, it has undergone numerous shifts of cash crops to sustain the economy with the oil palm as the latest crop. The palm oil industry has both novelty and challenges to thrive with the demand for sustainability. For the mandatory certification of Malaysia Sustainable Palm Oil, growers, mainly smallholders, faced restrictions on the certification process despite incentives from the federal government. This has put a setback to the effort by the palm oil industry in their commitment to being sustainable. In this study, the researchers plan to examine the palm oil industry's certification approach on the smallholders on their way to achieving a sustainable palm oil industry based on a case study approach. Therefore, the methodology for the study was using content analysis on public-domain literature found through electronic databases encompasses publications dating from 2000 to 2020. The study found that the acceptance and trust in smallholders' certification process are in correspond with the incomprehension and the certification process approach.